Obesity and atherosclerosis in children - Senka Mesihović-Dinarević (Medicinski glasnik, 2024)
Atherosclerosis, one of the leading causes of death in developed countries is characterized by lumen reduction of blood vessels due to local thickening of internal blood vessels caused by plaque/atheroma. It begins in childhood, goes for a long time without manifesting symptoms, increasing with age it begins to seriously threaten health. The most important risk factors for the development of atherosclerotic disease are: hyperlipidemia, hypertension, smoking, diabetes, high fibrinogen, excessive weight, increased level of homocysteine, physical inactivity, heredity and immune response in some diseases. The primary intention of prevention is to preclude the occurrence of risk factors for atherosclerosis, and the secondary is to prevent the development or aggravation of the illness along with the reduction or control of existing risks. There is an increasing number of studies that show that children are overweight, which in adolescence is certainly a risk factor for the onset of many chronic diseases, namely: cardiovascular, type 2 diabetes, orthopedic, and psychological diseases. The obesity epidemic is one of the most serious health problems of today affecting individuals of all ages. Atherosclerosis demands action with the aim of early detection and treatment as well as the reduction of development of risk factors for coronary artery diseases. Finding the most effective preventive measures for obesity in each country requires precise epidemiological data on the number of obese children and youth, as well as on their eating and activity habits.
Keywords: arteries; disease; overweight